NARAPIDANA YANG BERINTEGRASI DAN MENGURANGI RESIDIVIS DI LEMBAGA PEMASYARAKATAN KELAS IIA MATARAM - Somantri, Wahyu Abdillah; Yuska, Syahrial (Universitas Nusa Cendana, 2024)
Religious development in prisons is a way to make Correctional inmates become fully human beings who are aware of their mistakes, improve themselves to not repeat criminal acts, and are useful and play an active role in religion, nation, and state according to the goals of Correctional. However, in carrying out the coaching program, an evaluation needs to be carried out to determine the effectiveness of the program being run. Therefore, the Class IIA Mataram Prison needs to conduct a program evaluation to find out what things have gone well and are not enough to achieve the success of the coaching program. The purpose of this study is to find out what must be maintained and improved from the results of the program evaluation. Thus, researchers can provide a recommendation to improve the quality of the coaching program to achieve the objectives of the implementation of the religious development program in prisons. The data collection techniques used were observation, interview, and literature study. Data collection was carried out at the Mataram Class IIA Prison. This study concluded that the implementation of the Islamic boarding school-based religious development program at the Class IIA Mataram prison is quite good, but there are still obstacles in the implementation process. Keywords: Coaching; Evaluation; Recidivists